2011
DOI: 10.1071/wr10173
|View full text |Cite
|
Sign up to set email alerts
|

Does 'acoustic anchoring' reduce post-translocation dispersal of North Island robins?

Abstract: Context Animal translocations are an important conservation tool; however, post-release dispersal can hinder successful population establishment. Playback of conspecific song attracts dispersing individuals in some species, although its application following animal translocation has yet to be rigorously investigated. Aims To determine whether conspecific song can be used as an ‘acoustic anchor’, we adopted an experimental approach during the translocation of 60 North Island robins (Petroica longipes). Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…In particular, they should quantify habitat at release sites, including the ground layer, which is important for robin foraging but not assessed by us (e.g., see Recher et al 2002;Cousin 2004a;Antos et al 2008). We also suggest that playback of robin songs may increase the likelihood of robins remaining at release sites, as used by Bradley et al (2011).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In particular, they should quantify habitat at release sites, including the ground layer, which is important for robin foraging but not assessed by us (e.g., see Recher et al 2002;Cousin 2004a;Antos et al 2008). We also suggest that playback of robin songs may increase the likelihood of robins remaining at release sites, as used by Bradley et al (2011).…”
Section: Discussionmentioning
confidence: 95%
“…However, translocation and release into uninhabited sites have been used extensively with robins Petroica spp. in New Zealand, with high success (e.g., Armstrong and Ewen 2002;Armstrong and Davidson 2006;Bradley et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…comm. ; Bradley et al 2011), and captive-reared animals often have higher post-release mortality than wild animals (Snyder et al 1996). Ongoing research in this area will hopefully improve our predictive capabilities, but it would be rash at present to assume that any management will effectively reduce post-release dispersal or mortality unless this has been demonstrated in a similar species and system.…”
Section: Size and Composition Of Release Groupmentioning
confidence: 95%
“…Amongst songbirds, conspecific vocalizations have been effective attractants for translocation and anchoring (Ward & Schlossberg, ). A notable study on translocated New Zealand robins ( Petroica australis ), involved control sites and clearly demonstrated that more individuals returned to locations with conspecific playback (Bradley et al ., ). Marine animals have similar sensory constraints as seabirds and have also been studied from a sensory‐based conservation approach using auditory stimuli.…”
Section: Use and Effectiveness Of Sensory Modes In Conservationmentioning
confidence: 97%